KAJIAN KERAGAAN VARIETAS UNGGUL BARU PADI SAWAH DENGAN PENGELOLAAN TANAMAN TERPADU DI BANTUL, YOGYAKARTA - Bambang Sutaryo; Heni Purwaningsih (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2014)
The Assessment of Performance of High Yielding Variety Through Integrated Crop Management in Bantul, Yogyakarta. Study on performance for rice high yielding variety using five varieties namely Inpari 3, Inpari 4, Inpari 9, Inpari 10 and Inpari 11 through integrated crop management (ICM) was conducted at Pendowoharjo, Sewon, Bantul, Yogyakarta during the dry season of 2012. Seedling of 15 days with one seedling per hill was planted using “jajar legowo” 4:1 system, with plant spacing of 25 x 12.5 x 50 cm. Plot size per variety was 2000 m2. Ciherang and Situ Bagendit as populair varieties planted using the same population by farmers were used as control. Data were analyzed using t test. Inpari 10 gave the highest yield (9.5 t/ha) compared to check varieties and the other varieties tested, with yield ranging from 8.8 to 9.9 t/ha. The highest yield on Inpari 10 was contributed by the highest of the main yield components, namely the number of filled grains, total grain number, and the panicle number. All varieties showed early to moderate maturity, except Inpari 9 (125 days). Inpari 10 gave the highest profit compared with the others superior varieties tested and the most preferred by farmers because of more taste, more white color, more shiny, and more fragrant. Keywords: Inpari, Ciherang, Situ Bagendit,